Comparison of 18F-DCFPyL and 18F-FDG PET/computed tomography for the restaging of clear cell renal cell carcinoma: preliminary results of 15 patients. Issue 12 (December 2020) - Liu, Yachao; Wang, Guanyun; Yu, Hongkai; Wu, Yue; Lin, Mu; Gao, Jiangping; Xu, Baixuan
Abstract : Objectives: This study aimed to compare the diagnostic performance of 18 F-DCFPyL and 2-deoxy-2-[ 18 F]fluoro-D-glucose ( 18 F-FDG PET/computed tomography in the restaging of clear cell renal cell carcinoma after nephrectomy. Methods: In this retrospective study, a total of 15 patients with suspected local recurrence of clear cell renal cell carcinoma or metastasis after surgery underwent both 18 F-DCFPyL and 18 F-FDG PET/computed tomography. A systematic comparison of the maximum standardized uptake value and the target to background ratio was carried out between the lesions detected by the two tracers. Results: A total of 42 lesions were detected either by 18 F-DCFPyL PET/computed tomography or by 18 F-FDG PET/computed tomography. 18 F-DCFPyL PET/computed tomography, but not 18 F-FDG PET/computed tomography, accurately distinguished the two local recurrence from four postoperative changes. The remaining 36 lesions were soft tissue (14) and bone lesions (22); all 36 lesions were detected by 18 F-DCFPyL PET/computed tomography while only 10 (10/14) soft tissue lesions and 12 (12/22) bone lesions were detected by 18 F-FDG PET/computed tomography. The higher detection rate of soft tissue lesions using 18 F-DCFPyL PET/computed tomography was not statistically significant ( P = 0.125); however, 18 F-DCFPyL PET/computed tomography was statistically better ( P = 0.002) at detecting bone lesions. The average maximum standardized uptake value and target to background ratio of 18 F-DCFPyL were significantly higher than that of 18 F-FDG for soft tissue lesions (maximum standardized uptake value P = 0.005; target to background ratio P = 0.028) and bone lesions (maximum standardized uptake value P = 0.001; target to background ratio P = 0.001). Conclusions: Our preliminary results indicated that 18 F-DCFPyL PET/computed tomography is superior to 18 F-FDG PET/computed tomography for the detection of local recurrence at both the surgical site and in bone metastasis while the tracers are comparable in the detection of soft tissue metastases.